Performance characterization of Polylatic Acid (PLA) material manufactured by Fusion and Deposition Modeling (FDM) technology (Research, Society and Development, 2021)
The aim of this study was to characterize the performance of polylactic acid (PLA) material when manufactured by melt deposition modeling (FDM) technology. For the elaboration and organization of the experimental procedure, this study was constructed in accordance with the ASTM D3039/3039-95A standard, using a total of 36 specimens, modeled using Autodesk Inventor CAD software and later exported to CAM software Makerware, where parameters and processes for 3D printing were defined. The tensile tests were carried out on the EMIC DL 3000 machine, maintaining a standard condition with the laboratory at a temperature around 20°C. The values ​​defined as significant for this study were: Maximum Tension; Breaking Stress and Modulus of Elasticity. The manufactured specimens showed anisotropic behavior. In the stress-strain tests, the ruptures occurred in perfect profile rupture. The stress-strain curves showed practically no yield area. The deposition rates of 100% for the X axis showed higher rates for tensile strength as opposed to the 20% deposition rates for the Y axis. With regard to elongation, the parts with 20% deposition rate on the X axis had higher rates. Mechanical properties, tensile strength and flexural strength, increased with filling. PLA, manufactured using the FDM process, demonstrated better mechanical performance when produced on an X axis with 100% deposition rates for the structural internal fill and an extrusion temperature of 200°C. It is characterized as a typical polymeric brittle.